Do gaze and non-gaze stimuli trigger different spatial interference effects? It depends on stimulus perceivability - Chen, Zhe; Thomas, Rebecca H.; Chen, Makayla S. (Frontiers in Psychology, 2022)
Among the studies on the perception of gaze vs. non-gaze stimuli, some have shown that the two types of stimuli trigger different patterns of attentional effects, while others have reported no such differences. In three experiments, we investigated the role of stimulus perceivability in spatial interference effects when the targets were gaze vs. non-gaze stimuli. We used a spatial Stroop task that required participants to make a speeded response to the direction indicated by the targets located on the left or right side of fixation. In different experiments, the targets consisted of eyes, symbols, and/or arrows. The results showed that the magnitude of the spatial congruency effect differed between the types of targets when stimulus perceivability was not controlled. However, when the perceivability of the task relevant parts was comparable between the different types of targets, similar congruency effects were found regardless of target type. These results underscore the importance of controlling for stimulus perceivability, which is closely linked to the attentional zoom required to perform a task, when making inferences about the attentional mechanisms in the processing of gaze vs. non-gaze stimuli.